Antecedents of entrepreneurial and intrapreneurial intentions: evidence from Brazil - Marchiori, Danilo Magno; Madeira, Maria José Aguilar; Dinis, Anabela do Rosario Leitão (RACE - Revista de Administração, Contabilidade e Economia, 2018)
Abstract: The general objective of the present study is to identify the antecedents of the entrepreneurial and intrapreneurial intentions of 266 potential entrepreneurs, represented by students of the degree courses in Business Administration and Accounting Sciences in brazilians higher education institutions. For this purpose, as specific objectives we sought to identify whether entrepreneurial and intrapreneurial behavior are seen as different career options by students, as well as understanding the degree of relative importance for students of the attributes of property, income expectation, extra work tolerance, desire for autonomy and risk of income variation. For the data analysis, we specified structural equation models, with a confirmatory factorial analysis, as well as using the conjoint analysis approach of the attributes selected for the study. The results indicate that the constructive entrepreneurial intentions and intrapreneurial intentions are perceived as different career options by the students. The results also indicate that the most valued attribute by the respondents to define professional choice is income expectation and the least valued is the tolerance to the accomplishment of additional effort. Finally, the results point out that the income expectation variable is antecedent of the entrepreneurial intentions, and no other significant relationships were detected. Keywords: Entrepreneurial intentions. Intrapreneurial intentions. Intrapreneurship. Structural equation models. Conjoint analysis. Antecedentes das intenções empreendedoras e intraempreendedoras: evidências do Brasil Resumo: O objetivo geral com o presente estudo foi identificar os antecedentes das intenções empreendedoras e intraempreendedoras de 266 potenciais empreendedores, representados por estudantes dos cursos superiores de administração e ciências contábeis de instituições de ensino superior brasileiras. Para tanto, como objetivos específicos, buscou-se identificar se o comportamento empreendedor e o intraempreendedor são vistos como diferentes opções de carreira por estudantes, bem como compreender o grau de importância relativa para os estudantes dos atributos propriedade, expectativa de renda, tolerância ao trabalho extra, desejo de autonomia e risco de variação de renda. Para a análise dos dados foram especificados modelos de equações estruturais, com a realização de análise fatorial confirmatória, bem como utilizada a técnica da análise conjunta dos atributos selecionados para o estudo. Os resultados indicam que os construtos intenções empreendedoras e intenções intraempreendedoras são percebidos como diferentes opções de carreira pelos estudantes. Os resultados indicam, ainda, que o atributo mais valorizado pelos respondentes para a definição da escolha profissional foi a expectativa de renda, e o menos valorizado foi a tolerância à realização de esforço adicional. Por fim, os resultados apontaram que a variável expectativa de renda também é antecedente das intenções empreendedoras, não tendo sido detectadas outras relações significativas. Palavras-chave: Intenções empreendedoras. Intenções intraempreendedoras. Intraempreendedorismo. Modelos de equações estruturais. Análise conjunta.